Developing resilience among secondary school students in three Gombak secondary schools - Fontaine, Rodrigue Ancelot Harvey (KENMS-IIUM Press, 2013)
In 2013, this author approached three schools in Gombak and proposed an action learning project. Based on experience in IIUM, this author suggested that a project-based approach could be used to develop the potential of their students. Two schools agreed to participate. They selected students that they classified as being “problematic”. In 2014, from February to May, this author used 8 of his students to help 50 secondary school students to improve themselves. They were asked to make videos. The process of making these videos helped them to discover their hidden potential. The feedback of the teachers and the parents was that the children’s attitude had changed both at school and at home.